Instruction Task for Malay Phrase Boundary Annotation - Mohamed Hanum, Haslizatul; Atiqah Sia Abdullah, Nur; Abu Bakar, Zainab (International Journal of Engineering and Technology, 2018)
The paper presents a refined instruction task to assist evaluation of prosodic phrase (PPh) boundaries by naive listeners. The results from the perceptual experiments were compared to the boundaries produced by online automatic tagger. The Kappa evaluation shows the average of 85% on inter-rater agreement. More than 60% of the boundaries which are detected by the automatic tagger matched the reference boundaries, showing that the refined instruction task can be used to evaluate perception on phrase boundaries on continuous speech.Â Â